THE CATEGORY OF "ECOLOGICAL RESPONSIBILITY" IN THE ETHICAL TEACHING OF THE CATHOLIC CHURCH IN THE XXI CENTURY - Matyukhina, Oleksandra (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The category of ecological responsibility occupies one of the leading places in modern environmental ethics. The article examines the features of understanding the category in the ethical teaching of the Catholic Church. The aim and tasks. In this regard, the aim of the study is to determine the features of the approach to solving environmental problems in the social teaching of the Catholic Church. Separately, the category of "ecological responsibility" is highlighted, its place in the ethical teaching of the Church. Research methods are dictated by the subject of the study. Therefore, a sociocultural approach, structural, conceptual methods, and conceptual analysis are applied. Research results. Thus, the ways of overcoming the declarative nature of environmental legislation addressed to society and states as a whole, are determined. Discussion. The Church addresses man as a unique personality and assigns responsibility to him. Therefore, a change in the ecological paradigm can occur only on the basis of a change in the ethical paradigm, namely, the replacement of consumer values with human, humanistic ones. Conclusion. The Church's teaching of man emphasizes his dignity, the need for respect for life as holiness. In the encyclicals "Redemptor Hominis", "Evangelium Vitae" by John Paul II, "Laudate si" Francis I, environmentally responsible behavior aimed at preserving nature is considered to be a moral duty of every person, especially a believer. The freedom granted to him by God is inextricably linked with responsibility for all life in the world.